Brain malformation with loss of normal FGFR3 expression in thanatophoric dysplasia type I. Issue 6 (1st April 2013) - Itoh, Kyoko; Pooh, Ritsuko; Kanemura, Yonehiro; Yamasaki, Mami; Fushiki, Shinji
<x xml:space="preserve">Abstract</x> Thanatophoric dysplasia is a lethal form of chondrodysplastic dwarfism in which the cerebral cortex displays a unique and complex malformation. We report a female case of thanatophoric dysplasia type I (TD1) with FGFR3 mutation. In this case, fetal ultrasonography at the 18th week of gestation led to a prenatal diagnosis of TD1 with characteristic bone features. The subject was stillborn at the 21st week of gestation, showing marked shortening of the long bones, small thorax and curved short femurs, but without a cloverleaf skull. The temporal lobe was enlarged and hyperconvoluted, appearing as broad gyri and deep sulci, which were composed of focal polymicrogyria‐like shallow sulci and heterotopic neuroblastic nests in the intermediate zone and marginal zone. Abundant precursor cells, immunoreactive for nestin and Ki‐67 were observed with scattered mitoses in the thickened inner intermediate and subventricular zones of the temporal and occipital lobes. The cytoarchitecture from the entorhinal cortex to Ammon's horn was disorganized with leptomeningeal glioneuronal heterotopia, immunoreactive for doublecortin and nestin. The expression of FGFR3 was virtually not discernible in the temporal and occipital lobes or in the hippocampus. Genetic analysis revealed a point mutation at C8526T (R248C) in the exon 7 of FGFR3. This is the first report that demonstrates that overproduction of intermediate progenitor cells might be induced by FGFR3 mutation in a human TD1 case.